School Culture as a Pillar in Shaping the Discipline of Students at GIKI 1 Elementary School in Surabaya - Annisa Nur Balqis; Nafiah Nafiah; Akhwani Akhwani; Sri Hartatik (Electronic Journal of Education, Social Economics and Technology, 2025)
Discipline is one of the fundamental character traits that must be instilled from an early age, especially at the elementary school level. Therefore, school culture plays a crucial role in shaping students' character, including their sense of discipline. This study aims to describe the school culture implemented at SD Giki 1 Surabaya in developing students’ discipline character, as well as to identify the obstacles encountered in the process. This research uses a descriptive qualitative approach with a case study method. Data collection techniques include observation, in-depth interviews, and documentation involving the principal, teachers, and students from grades II and IV. The findings indicate that the development of discipline character at SD Giki 1 is carried out through the habituation of positive activities such as the 5S program (Smile, Greet, Salute, Polite, Courteous), morning literacy, Dhuha prayer, class cleaning duties, and adherence to school rules. However, the school faces challenges such as external environmental influences and inconsistent application of values at home. In conclusion, a consistent, well-structured school culture supported by all parties is effective in fostering students’ discipline character.